Faktor-Faktor yang Mempengaruhi Hasil Belajar Geografi secara Daring: Studi Siswa SMA Negeri 1 Samaturu, Sulawesi Tenggara - Andri Estining Sejati; Nasarudin Nasarudin; Ahmad Tarmizi Abd Karim; Agus Sugiarto; Eko Harianto; Sarwan Sarwan (JAMBURA GEO EDUCATION JOURNAL, 2023)
This study aimed to determine the factors of online geography learning outcomes in class XI IIS SMAN 1 Samaturu. Learning outcomes' position was crucial and inseparable from the learning process. Learning outcomes can be used as an indicator of the success of the learning process. Low learning outcomes were a problem in the learning process, which is still developing, and solutions or factors that influence learning outcomes have yet to be found. This type of research uses quantitative descriptive. The subject of this study was students of class XI IIS, totalling 33 students. The technique used to collect data was a questionnaire. First, data analysis was carried out by giving student scores for each questionnaire item. Second, averaging student scores for all of these items, and third, determining student criteria. The results of this study obtained that the student's geography learning outcomes factor was the parental attention factor found in the indicators of giving awards, giving punishments, giving examples, giving guidance and helping difficulties and meeting students' learning needs. The last two indicators make a major contribution to low student learning outcomes.